Variability of daptomycin MIC values for enterococcus faecium when measured by reference broth microdilution and gradient diffusion tests (2020)
Daptomycin has become a mainstay therapy for the treatment of serious vancomycin-resistant Enterococcus faecium infections. However, concern exists that current testing methods do not accurately predict the clinical success of daptomycin therapy. We evaluated a collection of 40 isolates of E. faecium across three centers by reference broth microdilution (BMD), and two gradient strips, to determine the precision of daptomycin MICs by these methods and the correlation of daptomycin MIC testing with mutations in the liaFSR system, one of the primary daptomycin resistance mechanisms among the enterococci. Daptomycin MICs spanned 3-log2 dilutions by BMD for 60.0% of isolates, 17.5% spanned 4 dilutions, 2.5% spanned 5 dilutions, and 20.0% spanned 6 or more dilutions. Fifteen isolates had MICs interpreted as susceptible by some tests and nonsusceptible by others. Neither BMD nor gradient diffusion tests could reliably differentiate isolates with or without mutations in liaFSR, resulting in a 59.8% very major error rate compared to determination of genotype by BMD, 63.5% by Etest, and 68.5% by MIC test strip. Imprecision in daptomycin MIC determination for E. faecium make establishment of a revised breakpoint challenging. Clinicians should be aware of this testing variability when making treatment decisions for patients with serious infections caused by this organism.